2018
DOI: 10.1016/j.amsu.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned postoperative reintubation following general and vascular surgical procedures: Outcomes and risk factors

Abstract: BackgroundUnplanned postoperative reintubation (UPR) is a marker for severe adverse outcomes following general and vascular surgery.Study designA retrospective analysis of 8809 adult patients, aged 18 years and older, who underwent major general and vascular surgery at a large single-center urban hospital was conducted from January 2013 to September 2016. Patients were grouped into those who experienced UPR and those who did not. Univariate and multivariate regression analyses were used to identify predictors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 22 publications
7
20
0
Order By: Relevance
“…Based on our results, age >65 yrs and ASA physical status 3 were identi ed as risk factors for unplanned reintubation caused by AAC. This result was in accordance with previous results that noted that advanced age and ASA physical status ≥3 should be considered independent risk factors for postoperative respiratory failure [7,8] . Age ≥65 was also shown to be an important risk factor for failed extubation in ICU patients [9] .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Based on our results, age >65 yrs and ASA physical status 3 were identi ed as risk factors for unplanned reintubation caused by AAC. This result was in accordance with previous results that noted that advanced age and ASA physical status ≥3 should be considered independent risk factors for postoperative respiratory failure [7,8] . Age ≥65 was also shown to be an important risk factor for failed extubation in ICU patients [9] .…”
Section: Discussionsupporting
confidence: 93%
“…Thus, FFP transfusion may be correlated with ARDS and reintubation after operation. RBC transfusion was not identi ed as an independent risk factor, consistent with the result from Acheampong D and colleagues [8] . A uid load ≥ 20 ml kg -1 was revealed as a risk factor in this study; however, other studies found that uid balance or overload was not a risk factor signi cant, possibly due to the different de nitions of uid load [12,20] .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Patients are usually extubated postoperatively once ventilatory support or airway protection needs subside. However, some patients cannot be weaned from mechanical ventilation during this period [1]. The risk factors for failure of extubation include old age, male gender, smoking, high American Society of Anesthesiologists (ASA) score, chronic obstructive pulmonary disease (COPD), congestive heart failure (CHF), and obesity [2].…”
Section: Introductionmentioning
confidence: 99%